Use of helicopters for retrieval of trauma patients: A geospatial analysis. Issue 1 (July 2019) - Smedley, W. Andrew; Stone, K. Lorraine; Brown, Allison; Farley, Paige; Griffin, Russell L.; Cox, Daniel B.; Kerby, Jeffrey D.; Jansen, Jan O.
Abstract : BACKGROUND: Helicopters are widely used to facilitate the transport of trauma patients, from the scene of an incident to the hospital. However, the use of helicopters may not always be appropriate. The aim of this project was to conduct a geospatial analysis of helicopter transport to a Level I trauma center. METHODS: Retrospective geospatial analysis of trauma registry data, 2013 to 2018. We included all adult (≥16) trauma patients brought to the trauma center directly from the scene. Data were geocoded and analyzed using arcGIS. Drive times and flight times were calculated using Google Maps. Flight times included the time required to reach the incident location. RESULTS: Two thousand eight hundred ninety-three patients were identified, and 1, 911 had incident locations recorded and were therefore included in the analysis. The median age was 41 years (interquartile range [IQR], 27–58 years). Twenty-four percent of the patients had suffered severe injuries (Injury Severity Score [ISS], 16–25), 17% very severe injuries (ISS > 25), 24% moderately severe injuries, and 36% minor injuries (ISS, 1–8). The overall geographical distribution was centroidal, although with a concentration of case volume in the vicinity, and to the northeast, of the trauma center. Median flight time was 60 minutes (IQR, 52–69 minutes), and median drive time 65 minutes (IQR, 54–86 minutes). In 33% of the patients, the calculated drive time to the trauma center was shorter than the calculated flight time when considering the time for the helicopter to reach the scene. CONCLUSION: The majority of patients taken to our level I trauma center by helicopter are injured in relatively close proximity. One in four patients is severely or very severely injured, but one third of the patients have only minor injuries. Over a quarter of trauma patients might have reached hospital more quickly if they had been taken by road, rather than helicopter. LEVEL OF EVIDENCE: Epidemiological/geographical study, level V.